What Drives Life-History Variation in the Livebearing Fish Poeciliopsis prolifica? An Assessment of Multiple Putative Selective Agents - Roth-Monzón, Andrea J.; Belk, Mark C.; Zúñiga-Vega, J. Jaime; Johnson, Jerald B. (Frontiers in Ecology and Evolution, 2021)
Life-history traits are directly linked to fitness, and therefore, can be highly adaptive. Livebearers have been used as models for understanding the evolution of life histories due to their wide diversity in these traits. Several different selective pressures, including density, predation, and resource levels, can shape life-history traits. However, these selective pressures are usually considered independently in livebearers and we lack a clear understanding of how they interact in shaping life-history evolution. Furthermore, selective pressures such as interspecific competition are rarely considered as drivers of life-history evolution in poeciliids. Here we test the simultaneous effects of several potential selective pressures on life-history traits in the livebearing fish Poeciliopsis prolifica. We employ a multi-model inference approach. We focus on four known agents of selection: resource availability, stream velocity, population density, and interspecific competition, and their effect on four life-history traits: reproductive allocation, superfetation, number of embryos, and individual embryo size. We found that models with density and interspecific competition alone were strongly supported in our data and, hence, indicated that these two factors are the most important selective agents for most life-history traits, except for embryo size. When density and interspecific competition increase there is an increase in each of the three life-history traits (reproductive allocation, superfetation, number of embryos). For individual embryo size, we found that all single-agent models were equivalent and it was unclear which selective agent best explained variation. We also found that models that included density and interspecific competition as direct effects were better supported than those that included them as indirect effects through their influence on resource availability. Our study underscores the importance of interspecific competitive interactions on shaping life-history traits and suggests that these interactions should be considered in future life-history studies.